2021
DOI: 10.3390/ijerph18179215
|View full text |Cite
|
Sign up to set email alerts
|

Missing In-Center Hemodialysis Sessions among Patients with End Stage Renal Disease in Banda Aceh, Indonesia

Abstract: Indonesian universal health coverage was implemented in 2013 and hemodialysis services became universally accessible, yet few studies have examined patient adherence to hemodialysis schedules. We examined the rates of missed in-center hemodialysis sessions in Banda Aceh and the factors associated with non-attendance. This cross-sectional questionnaire survey included 193 patients receiving in-center hemodialysis. Approximately 28% of the patients missed ≥ 1 hemodialysis session in the month prior to the questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…In contrast, Liu et al found that a lack of knowledge about kidney disease and the importance of HD treatment led to missed dialysis sessions. 52 Likewise, Rose et al reported that a knowledge deficit among individuals with chronic heart failure was associated with non-participation in a cardiac rehabilitation program. 53 It is important to note that patients’ knowledge is minimal upon the onset of ESRD.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Liu et al found that a lack of knowledge about kidney disease and the importance of HD treatment led to missed dialysis sessions. 52 Likewise, Rose et al reported that a knowledge deficit among individuals with chronic heart failure was associated with non-participation in a cardiac rehabilitation program. 53 It is important to note that patients’ knowledge is minimal upon the onset of ESRD.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study revealed that 33% of these patients had poor adherence to fluid restriction 44 . Another study also found that one-fourth of patients with end-stage renal disease had a history of absence from hemodialysis sessions during the past month 45 . Generally speaking, estimations show that non-adherence to medication regimens among these patients varies from 3 to 80% 46 .…”
Section: Introductionmentioning
confidence: 92%
“…The rise in prevalence of kidney diseases such as CKD and ESRD among global public health concerns have resulted in significant problem, which has resulted in several negative consequences, including weakness, swelling, poor sleep, nausea, coma, and eventually death [ 1 4 ]. Patients with these complications will require dialysis or a kidney transplant [ 1 , 2 ].…”
Section: Surface Plasmon Resonance (Spr): Theory and Working Principlementioning
confidence: 99%
“…According to global estimates, approximately 4.902 to 7.083 million people require kidney transplant surgery [ 3 ]. From 2010 to 2017, the number of ESRD and prevalent cases in Indonesia increased significantly, from 9649 to 30831 cases and from 11484 to 77892 cases, respectively [ 4 ]. The kidneys are vital organs that never stop filtering the blood of numerous wastes and toxic substances and removing them via urine while returning essential substances such as vitamins, amino acids, glucose, and hormones to the bloodstream [ 5 ].…”
Section: Introductionmentioning
confidence: 99%